A STUDY OF STRESS CORROSION CRACKING RESISTANCE FOR COLD FORMING PLASTIC DEFORMED Cu-30Zn ALLOY - Gadang Priyotomo; Akhmad Faizal; Rini Riastuti (Widyariset, 2018)
Cu-30Zn alloy has good atmospheric corrosion resistance. It is mainly used as automotive radiator cores, ammunition component, lamp fixture, flashlight shells and kickplates. Cold rolled Cu-30Zn with deformation degree 33,87% at 300OC was tested its Stress Corrosion Cracking (SCC) property. Stress corrosion cracking (SCC) of a Cu–30Zn has been investigated using Mattsson solutions 0,5 M (NH4)2SO4 + 0,05 M CuSO4 in room temperature by using a constant load method. Cu-30Zn has a weakness on stress corrosion cracking in ammonia environment (mattson solution). Scanning electron microscope (SEM) testing indicated the failure of cold roll Cu-30Zn was a transgranular cracking. Furthermore, cracking occued at stress below yield stress. Energy dispersive Spectroscopy (EDS) test exhibited dezincification indication on fracture surface. The visual examination of surface morphology on alloy showed discoloration from yellow to red. Homogenized Cu-30Zn showed better SCC resistance than cold rolled Cu-30Zn.